Fixed Asset Management in the Perspective of Auditing and Accounting Standards: a Study at the Tarakan City Transportation Office - Syahrial Maulana; Iqrima Mas Mappangile (SEAN Institute, 2026)
Fixed assets are a vital component of government financial statements, holding significant value and strategic roles in supporting organizational operations. The complexity of their recording, valuation, and presentation makes fixed assets a central concern in public sector accounting practices. This study aims to analyze the accounting treatment of fixed assets at the Department of Transportation of Tarakan City based on Government Accounting Standards Statement (PSAP) No. 07. This research employs a qualitative approach using literature review and document analysis techniques. The results show that although the Department of Transportation has implemented most provisions of PSAP No. 07, several issues remain, such as inconsistent asset recording and inadequate asset valuation practices. These findings highlight the need to improve fixed asset management systems to enhance the transparency and accountability of regional financial management.